Exploring the experiences of people and family carers from under-represented groups in self-managing Parkinson's disease and their use of digital health to do this. (May 2022) - Nimmons, Danielle; Armstrong, Megan; Pigott, Jennifer; Walters, Kate; Schrag, Anette; Ogunleye, Della; Dowridge, Wesley; Read, Joy; Davies, Nathan
Introduction: Digital health is thought to enable people to better manage chronic conditions, such as Parkinson's. However, little is known about how people from under-represented groups with chronic conditions use digital health to self-manage. Objective: The objective of our study was to explore the experiences of people and family carers from under-represented groups in self-managing Parkinson's, including their use of digital health to do this. Methods: Semi-structured interviews (n = 18, including four dyadic) were conducted remotely, with 16 people with Parkinson's and six family carers in 2020–2021. Participants were purposively sampled from under-represented groups: belong to an ethnic minority, or having significant physical or sensory impairment. Interviews were audio-recorded, transcribed and analysed using thematic analysis. Results: Three main themes of importance were developed: 'self-management support', 'digital health use to support self-management' and 'identity, attitudes and characteristics'. Participants received medical, psychological, social and practical self-management support. Some participants used digital health resources, e.g., Parkinson's UK website. Digital literacy was the biggest barrier to using digital health, regardless of background, often dependant on previous occupation and confidence. Few ethnic minority participants thought race or culture alters self-management ability and most believed there was no need for digital health interventions to be tailored to an individual's race or culture. Some felt inclusivity was important in terms of diverse images of people. A range of considerations were identified to optimise digital health, such as assistive equipment for people with sensory impairment. Conclusions: Barriers to using digital health for self-management were primarily dependent on personal factors including digital literacy and attitudes but rarely race or culture. We recommend the optimisation of digital health interventions by providing assistive technology at low cost, and visual inclusiveness should be promoted by including images of people from diverse backgrounds.